Design of a wall-climbing robot with passive suction cups - Yoshida, Yu; Shugen Ma (2010 IEEE International Conference on Robotics and Biomimetics, 2010)
This paper presents a wall-climbing robot which adopts passive suction cups as the attaching components. Using only one motor, this robot can not only move on a wall but also attach suction cups to the wall and remove them from the wall. Passive suction cups do not consume additional energy to keep adhesion. Therefore, the proposed robot can realize the climbing motion on a wall with relatively low energy consumption. The prototype has been designed, fabricated and tested. The experiments showed that the proposed robot could attach and remove suction cups passively. However, the robot could not move up the wall well and fell down often. In order to solve this problem, the load of each suction cup when attached to a vertical wall is analyzed. As a result, it is shown that a moment generated by both of the gravity and the attaching force of suction cups turns the robot down from the wall. Then a new model which improves the falling problems is thus designed.